Case report: Early molecular confirmation and sodium polystyrene sulfonate management of systemic pseudohypoaldosteronism type I - Alkhatib, Einas H.; Bartlett, Deirdre; Kanakatti Shankar, Roopa; Regier, Debra; Merchant, Nadia (Frontiers in Endocrinology, 2024)
Established Facts• Type 1 pseudohypoaldosteronism (PHA) consists of resistance to aldosterone; neonatal presentation is characterized by salt wasting, hyperkalemia, and metabolic acidosis with high risk of mortality.• Type 1 PHA can be autosomal dominant (renal type 1) or autosomal recessive (systemic type 1); renal PHA can be feasibly managed with salt supplementation, whereas systemic PHA can be more refractory to treatment.• Sodium polystyrene sulfonate can effectively treat hyperkalemia in type 1 PHA when it is safely decanted into feeds.• Early molecular confirmation in the NICU/inpatient setting is instrumental in guiding definitive treatment approaches.